Management of vitiligo amidst the COVID-19 pandemic: A survey and resulting consensus - Manas Chatterjee; Anupam Das (Wolters Kluwer Medknow Publications, 2021)
Background: COVID-19 pandemic has changed the approach of dermatologists, with respect to management of numerous conditions, vitiligo being one of them. However, there is a lack of consensus on how to deal with patients of vitiligo, as we battle this pandemic. Aim: To conduct a questionnaire-based survey, amongst expert dermatologists; in order to understand the impact of COVID-19 on the management of vitiligo. Materials and Methods: An online semi-structured English questionnaire was prepared and the link was circulated among 50 pan-Indian expert dermatologists, through various platforms (snowball sampling). Confidentiality and anonymity were strictly maintained. Responses were analyzed at the end of the study and a consensus statement was generated. Results: 42.22% of the respondents believed that teleconsultation is adequate for the diagnosis and management of most cases of vitiligo. 64.44% were found to be comfortable in prescribing oral medications, even during the COVID-19 pandemic; of which 62% would prefer to prescribe systemic steroids; followed by 17%, 11%, 7%, and 3% who would prefer cyclosporine, azathioprine, mycophenolate mofetil, and methotrexate, respectively. 64.44% respondents would recommend phototherapy in their office and 80% would prefer home-based phototherapy (PUVAsol or handheld NBUVB devices). 86.67% would prefer to stop the oral immunosuppressive drugs, till the COVID-19 RTPCR positive patients are tested negative. Limitations: The results are based on a survey of a small albeit selected group of dermatologists who decided on the currently available information on COVID-19. The same may change depending on the nature of further available information on the virus and its effect on how we manage the patients. Conclusions: Cases for initial consultation may be seen physically, and those for follow-up may be scheduled for teleconsultation. Topical therapy may be used without any hesitation. Phototherapy may be best advised with either PUVAsol or home-based phototherapy units (handheld NBUVB devices). With regards to systemic immunosuppressives, oral minipulse therapy may be preferable in view of lesser requirement of monitoring. Surgery for vitiligo should be performed only if the psychological well-being is severely affected.